Cover Image, Volume 85, Issue 1, January 2018. Issue 1 (12th February 2018) - Shin, Min‐Young; Lee, Seung‐Eun; Son, Yeo‐Jin; Park, Yun‐Gwi; Jeong, Sang‐Gi; Kim, Eun‐Young; Park, Se‐Pill
Abstract : The cover image, by Min‐Young Shin et al., is based on the Original Article Lysophosphatidic acid accelerates development of porcine embryos by activating formation of the blastocoel, DOI:10.1002/mrd.22938 .